Living Hadith as an Interdisciplinary Approach: Integration between Textual Studies, Anthropology, and Sociology of Religion - Syaifudin, Muh.; Sholihah, Izzatus (SAMAWAT: JOURNAL OF HADITH AND QURANIC STUDIES, 2025)
This study explores Living Hadith as an interdisciplinary field that bridges textual scholarship, anthropology, and sociology of religion. The research argues that Living Hadith—the study of how prophetic traditions (hadith) are lived, interpreted, and practiced within Muslim societies—requires methodological pluralism to capture its textual depth and social dynamism. Drawing from ethnographic data and textual analyses of Living Hadith practices in Indonesia, including ritual recitations, communal commemorations (maulid), and everyday religious expressions, this study reveals how lived interpretations of hadith transform scriptural authority into cultural performance. By integrating textual hermeneutics with anthropological fieldwork and sociological analysis, the paper demonstrates how Living Hadith functions as both a moral discourse and a social institution that shapes Muslim identity. The findings highlight that interdisciplinarity is not merely an academic method but an epistemological necessity for understanding the social life of hadith. Through Indonesian case studies—particularly from Java, Aceh, and Minangkabau—the article offers a model for future Living Hadith research that combines textual fidelity with ethnographic insight and sociological theory.